Synthesis of Curcumin Derivatives via Knoevenagel Reaction Within a Continuously Driven Microfluidic Reactor Using Polymeric Networks Containing Piperidine as a Catalyst - Killi, Naresh; Rumpke, Katja; Kuckling, Dirk (Gels)
The use of organo-catalysis in continuous-flow reactor systems is gaining attention in medicinal chemistry due to its cost-effectiveness and reduced chemical waste. In this study, bioactive curcumin (CUM) derivatives were synthesized in a continuously operated microfluidic reactor (MFR), using piperidine-based polymeric networks as catalysts. Piperidine methacrylate and piperidine acrylate were synthesized and subsequently copolymerized with complementary monomers (MMA or DMAA) and crosslinkers (EGDMA or MBAM) via photopolymerization, yielding different polymeric networks. Initially, batch reactions were optimized for the organo-catalytic Knoevenagel condensation between CUM and 4-nitrobenzaldehyde, under various conditions, in the presence of polymer networks. Conversion was assessed using offline 1H NMR spectroscopy, revealing an increase in conversion with enhanced swelling properties of the polymer networks, which facilitated greater accessibility of catalytic sites. In continuous-flow MFR experiments, optimized polymer gel dots exhibited superior catalytic performance, achieving a conversion of up to 72%, compared to other compositions. This improvement was attributed to the enhanced swelling in the reaction mixture (DMSO/methanol, 7:3 v/v) at 40 °C over 72 h. Furthermore, the MFR system enabled the efficient synthesis of a series of CUM derivatives, demonstrating significantly higher conversion rates than traditional batch reactions. Notably, while batch reactions required 90% catalyst loading in the gel, the MFR system achieved a comparable or superior performance with only 50% catalyst, resulting in a higher turnover number. These findings underscore the advantages of continuous-flow organo-catalysis in enhancing catalytic efficiency and sustainability in organic synthesis.
Keywords: flow chemistry; heterogeneous catalysis; sustainable synthesis; organo-catalysis; polymeric gel dots

Advanced thermomechanical flow forming: A novel approach to α’-martensite control for enhanced material properties - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank (Materials Research Proceedings)
Abstract. Flow forming is recognized for its precision in producing rotationally symmetric components, but the use of metastable austenitic stainless steel (AISI 304L) introduces challenges due to uncontrolled strain-induced α’ martensite formation. Variations in factors such as eccentricity and batch inconsistencies lead to unpredictable microstructural profiles, limiting reproducibility [1,2]. This study addresses these issues by incorporating thermal actuators for cryogenic cooling and induction heating to regulate forming temperatures, enabling control of the α’-martensite content. Experimental investigations demonstrate that local tempering during thermomechanical reverse flow forming produces discernible variations in microstructure, affecting mechanical and magnetic properties [3]. Controlled local adjustments of α’-martensite content allow for customization of properties in seamless tubes, advancing manufacturing capabilities for complex, defect-free components. The results presented demonstrate promising strategies for implementation within the context of closed-loop property control in flow forming.
Keywords: Flow Forming; Thermomechanical Forming; α’-Martensite; Property Control

New pressure drop and heat transfer correlations for turbulent forced convection in internally channeled tube heat exchanger ducts - Al-Lami, Abbas J.S.; Kenig, Eugeny Y. (Case Studies in Thermal Engineering)
Keywords: Fluid Flow and Transfer Processes; Engineering (miscellaneous)

Selective Discrimination between CO and H2 with Copper–Ceria-Resistive Gas Sensors - Baier, Dominik; Priamushko, Tatiana; Weinberger, Christian; Kleitz, Freddy; Tiemann, Michael (ACS Sensors)
The production of hydrogen and the utilization of biomass for sustainable concepts of energy conversion and storage require gas sensors that discriminate between hydrogen (H2) and carbon monoxide (CO). Mesoporous copper–ceria (Cu–CeO2) materials with large specific surface areas and uniform porosity are prepared by nanocasting, and their textural properties are characterized by N2 physisorption, powder XRD, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The oxidation states of copper (Cu+, Cu2+) and cerium (Ce3+, Ce4+) are investigated by XPS. The materials are used as resistive gas sensors for H2 and CO. The sensors show a stronger response to CO than to H2 and low cross-sensitivity to humidity. Copper turns out to be a necessary component; copper-free ceria materials prepared by the same method show only poor sensing performance. By measuring both gases (CO and H2) simultaneously, it is shown that this behavior can be utilized for selective sensing of CO in the presence of H2.
Keywords: Fluid Flow and Transfer Processes; Process Chemistry and Technology; Instrumentation; Bioengineering

Joining of CFRT/Steel Hybrid Parts via Direct Pressing of Cold Formed Non-Rotational Symmetric Pin Structures - Popp, Julian; Römisch, David; Merklein, Marion; Drummer, Dietmar (Applied Sciences)
In this study, quasi-unidirectional continuous fiber reinforced thermoplastics (CFRTs) are joined with metal sheets via cold formed cylindrical, elliptical and polygonal pin structures which are directly pressed into the CFRT component after local infrared heating. In comparison to already available studies, the unique novelty is the use of non-rotational symmetric pin structures for the CFRT/metal hybrid joining. Thus, a variation in the fiber orientation in the CFRT component as well as a variation in the non-rotational symmetric pins’ orientation in relation to the sample orientation is conducted. The created samples are consequently mechanically tested via single lap shear experiments in a quasi-static state. Finally, the failure behavior of the single lap shear samples is investigated with the help of microscopic images and detailed photographs. In the single lap shear tests, it could be shown that non-rotational symmetric pin structures lead to an increase in maximum testing forces of up to 74% when compared to cylindrical pins. However, when normalized to the pin foot print related joint strength, only one polygonal pin variation showed increased joint strength in comparison to cylindrical pin structures. The investigation of the failure behavior showed two distinct failure modes. The first failure mode was failure of the CFRT component due to an exceedance of the maximum bearing strength of the pin-hole leading to significant damage in the CFRT component. The second failure mode was pin-deflection due to the applied testing load and a subsequent pin extraction from the CFRT component resulting in significantly less visible damage in the CFRT component. Generally, CFRT failure is more likely with a fiber orientation of 0° in relation to the load direction while pin extraction typically occurs with a fiber orientation of 90°. It is assumed that for future investigations, pin structures with an undercutting shape that creates an interlocking joint could counteract the tendency for pin-extraction and consequently lead to increased maximum joint strengths.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Hot Spinning of Cutting Blades for Food Industry - Engemann, David; Homberg, Werner
The spinning process is a flexible incremental forming process for the manufacturing of axially-symmetric sheet metal or tubular components with functionally graded properties. It is characterized by the utilization of universal tooling geometries and quite low forming forces. The process has a high potential to reduce material waste, to extend the forming limits and to achieve more complex geometries as well as favorable part properties [1]. Current research work at the Chair of Forming Technology (LUF) is focused on innovative flow-turning processes that have a high potential for producing flat components with excellent geometrical and mechanical properties while keeping process times short [2]. In combination with process-integrated local heat treatment, the new spinning process is predestined for the efficient forming of ultra-high-strength steel or tailored materials. Due to the desired field of food industry only food-safe materials such as special stainless steels are being investigated. This paper presents an innovative machine layout as well as an adequate process design for the production of high-performance circular knives with optimized mechanical hardness. In this context, particular attention is paid to various areas of temperature control as well as process-related challenges during the process.
Keywords: Cutting blades; Flow-forming; Incremental forming; Hot Forming; High strength steels

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Bound state solutions of Dirac equation: spin and pseudo-spin symmetry in the presence of the combined Manning–Rosen and Yukawa tensor potentials - Ahmadov, A. I.; Nagiyev, Sh. M.; Aydin, C.; Tarverdiyeva, V. A.; Orujova, M. Sh.; Badalov, S. V. (The European Physical Journal Plus)
Keywords: General Physics and Astronomy; Fluid Flow and Transfer Processes

Proactive Management of Requirement Changes in the Development of Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Preuß, Daniel (Applied Sciences)
Requirement changes and cascading effects of change propagation are major sources of inefficiencies in product development and increase the risk of project failure. Proactive change management of requirement changes yields the potential to handle such changes efficiently. A systematic approach is required for proactive change management to assess and reduce the risk of a requirement change with appropriate effort in industrial application. Within the paper at hand, a novel method for Proactive Management of Requirement Changes (ProMaRC) is presented. It is developed in close collaboration with industry experts and evaluated based on workshops, pilot users’ feedback, three industrial case studies from the automotive industry and five development projects from research. To limit the application effort, an automated approach for dependency analysis based on the machine learning technique BERT and semi-automated assessment of change likelihood and impact using a modified PageRank algorithm is developed. Applying the method, the risks of requirement changes are assessed systematically and reduced by means of proactive change measures. Evaluation shows high performance of dependency analysis and confirms the applicability and usefulness of the method. This contribution opens up the research space of proactive risk management for requirement changes which is currently almost unexploited. It enables more efficient product development.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Learning Flow Scheduling - Hasnain, Asif; Karl, Holger (2021 IEEE 18th Annual Consumer Communications & Networking Conference (CCNC))
Datacenter applications have different resource requirements from network and developing flow scheduling heuristics for every workload is practically infeasible. In this paper, we show that deep reinforcement learning (RL) can be used to efficiently learn flow scheduling policies for different workloads without manual feature engineering. Specifically, we present LFS, which learns to optimize a high-level performance objective, e.g., maximize the number of flow admissions while meeting the deadlines. The LFS scheduler is trained through deep RL to learn a scheduling policy on continuous online flow arrivals. The evaluation results show that the trained LFS scheduler admits 1.05x more flows than the greedy flow scheduling heuristics under varying network load.
Keywords: Flow scheduling; Deadlines; Reinforcement learning

Anomalous bulk diffusion of methylene diphenyl diisocyanate in silicone elastomer - Wortmann, Martin; Viertel, Klaus; Welle, Alexander; Keil, Waldemar; Frese, Natalie; Hachmann, Wiebke; Krieger, Philipp; Brikmann, Johannes; Schmidt, Claudia; Moritzer, Elmar; Hüsgen, Bruno (International Journal of Heat and Mass Transfer)
Keywords: Fluid Flow and Transfer Processes; Mechanical Engineering; Condensed Matter Physics

Forming of metastable austenitic stainless steel tubes with axially graded martensite content by flow-forming - Arian, Bahman; Homberg, Werner; Riepold, Markus; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank
One of the main objectives of production engineering is to reproducibly manufacture (complex) defect-free parts. To achieve this, it is necessary to employ an appropriate process or tool design. While this will generally prove successful, it cannot, however, offset stochastic defects with local variations in material properties. Closed-loop process control represents a promising approach for a solution in this context. The state of the art involves using this approach to control geometric parameters such as a length. So far, no research or applications have been conducted with closed-loop control for microstructure and product properties. In the project on which this paper is based, the local martensite content of parts is to be adjusted in a highly precise and reproducible manner. The forming process employed is a special, property-controlled flow-forming process. A model-based controller is thus to generate corresponding correction values for the tool-path geometry and tool-path velocity on the basis of online martensite content measurements. For the controller model, it is planned to use a special process or microstructure (correlation) model. The planned paper not only describes the experimental setup but also presents results of initial experimental investigations for subsequent use in the closed-loop control of α’-martensite content during flow-forming.
Keywords: Flow-forming; Spinning; Process Strategy; Martensite Content; Property Control; Micromagnetic Measurement; Metastable Austenitic Stainless Steel

Some ideas for the further development of hydroforming process chains - Wiens, Eugen; Djakow, Eugen; Homberg, Werner (Nebu/Nehy 2020)
Even though the spectrum of parts is expected to shift over the long term as a result of increasing e-mobility, there is still an extremely high demand for complex components made of high-strength materials which can only be produced by hydroforming technologies. The innovative combination of hydroforming processes with other forming processes, as well as the improvement of the processes themselves, offers considerable potential for improvement. A number of promising ways of improving the hydroforming process chain are therefore the subject of this contribution. The focus of the article is on possible approaches for combining (incremental) pre- and post-forming operations, which can permit considerable improvements in both quality and features at a reduced cost. Furthermore, a novel combination of quasi-static and high-speed forming processes is presented, leading to an improved overall forming process (with a high application potential) for the production of complex parts.
Keywords: Hydroforming; Incremental Forming; Internal Flow-turning; High-speed Forming

Removing Undesirable Flows by Edge Deletion - Polevoy, Gleb; Trajanovski, Stojan; Grosso, Paola; de Laat, Cees (Combinatorial Optimization and Applications)
Consider mitigating the effects of denial of service or of malicious traffic in networks by deleting edges. Edge deletion reduces the DoS or the number of the malicious flows, but it also inadvertently removes some of the desired flows. To model this important problem, we formulate two problems: (1) remove all the undesirable flows while minimizing the damage to the desirable ones and (2) balance removing the undesirable flows and not removing too many of the desirable flows. We prove these problems are equivalent to important theoretical problems, thereby being important not only practically but also theoretically, and very hard to approximate in a general network. We employ reductions to nonetheless approximate the problem and also provide a greedy approximation. When the network is a tree, the problems are still MAX SNP-hard, but we provide a greedy-based 2l-approximation algorithm, where l is the longest desirable flow. We also provide an algorithm, approximating the first and the second problem within {\$}{\$}2 {\backslash}sqrt{\{} 2{\backslash}left| E {\backslash}right| {\}}{\$}{\$}and {\$}{\$}2 {\backslash}sqrt{\{}2 ({\backslash}left| E {\backslash}right| + {\backslash}left| {\backslash}text {\{}undesirable flows{\}} {\backslash}right| ){\}}{\$}{\$}, respectively, where E is the set of the edges of the network. We also provide a fixed-parameter tractable (FPT) algorithm. Finally, if the tree has a root such that every flow in the tree flows on the path from the root to a leaf, we solve the problem exactly using dynamic programming.
Keywords: flow; Red-Blue Set Cover; Positive-Negative Partial Set Cover; approximation; tree; MAX SNP-hard; root; leaf; dynamic programming; FPT

Digitalisierungspotenziale in Geschäftsprozessen effizient und effektiv erkennen (Effective and Efficient Identification of Digitalization Potentials in Business Processes) - Rittmeier, Florian; Engels, Gregor; Teetz, Alexander (Joint Proceedings of the Workshops at Modellierung 2018 co-located with Modellierung 2018, Braunschweig, Germany, February 21, 2018.)
Ein wichtiges Element der Digitalen Transformation ist die Digitalisierung der Prozesse in Unternehmen. Eine Herausforderung besteht hierbei in der systematischen Erkennung von Digitalisierungspotenzialen in Prozessen. Bestehende Ansätze benötigen Experten, welche Potenziale über ihre Erfahrung oder zeitaufwendig mithilfe von Musterkatalogen identifizieren. In diesem Artikel werden verschiedene Digitalisierungspotenziale klassifiziert und Muster für ein zukünftiges musterbasiertes Analyseverfahren zur automatisierten Identifikation von Digitalisierungspotenzialen in BPMN-Diagrammen beschrieben. Im Vergleich zu bestehenden Ansätzen erlaubt es Experten die Identifizierung von Digitalisierungspotenzialen effizienter und effektiver durchzuführen.
Keywords: Digitalisierungspotenziale; BPI; Digitale Transformation; Information Flow-Modellierung; Patterns; Requirements Engineering

Measures of Edge-Uncolorability of Cubic Graphs - Fiol, M. A.; Mazzuoccolo, Guiseppe; Steffen, Eckhard (The Electronic Journal of Combinatorics)
There are many hard conjectures in graph theory, like Tutte's 5-flow conjecture, and the 5-cycle double cover conjecture, which would be true in general if they would be true for cubic graphs. Since most of them are trivially true for 3-edge-colorable cubic graphs, cubic graphs which are not 3-edge-colorable, often called snarks, play a key role in this context. Here, we survey parameters measuring how far apart a non 3-edge-colorable graph is from being 3-edge-colorable. We study their interrelation and prove some new results. Besides getting new insight into the structure of snarks, we show that such measures give partial results with respect to these important conjectures. The paper closes with a list of open problems and conjectures.
Keywords: Cubic graph; Tait coloring; Snark; Boole coloring; Berge's conjecture; Tutte's 5-flow conjecture

Filtering Undesirable Flows in Networks - Polevoy, Gleb; Trajanovski, Stojan; Grosso, Paola; de Laat, Cees (Combinatorial Optimization and Applications: 11th International Conference, COCOA 2017, Shanghai, China, December 16-18, 2017, Proceedings, Part I)
Keywords: flow; filter; MMSA; set cover; approximation; local ratio algorithm

Bank funding stability, pricing strategies and the guidance of depositors - Schlueter, Tobias; Sievers, Sönke; Hartmann-Wendels, Thomas (Journal of Banking & Finance (VHB-JOURQUAL 4 Ranking A))
Banks face a 'behavioralization' of their balance sheets since deposit funding increasingly consists of non-maturing deposits with uncertain cash flows exposing banks to asset liability (ALM) risk. Thus, this study examines the behavior of banks’ retail customers regarding non-maturing deposits. Our unique sample comprises the contract and cash flow data for 2.2 million individual contracts from 1991 to 2010. We find that contractual rewards, i.e., qualified interest payments, and government subsidies, effectively stabilize saving behavior and thus bank funding. The probability of an early deposit withdrawal decreases by approximately 40%, and cash flow volatility drops by about 25%. Our findings provide important insights for banks using pricing incentives to steer desired saving patterns for their non-maturing deposit portfolios. Finally, these results are informative regarding the bank liquidity regulations (Basel III) concerning the stability of deposits and the minimum requirements for risk management (European Commission DIRECTIVE 2006/48/EC).
Keywords: retail saving behavior; non-maturing deposits; deposit funding; contractual rewards; interest rate bonus; saving persistence; cash flow volatility

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, R.; Nudelman, I.; Polevoy, Gleb (Networking, IEEE/ACM Transactions on)
In this paper, we define and study a new problem, referred to as the Dependent Unsplittable Flow Problem (D-UFP). We present and discuss this problem in the context of large-scale powerful (radar/camera) sensor networks, but we believe it has important applications on the admission of large flows in other networks as well. In order to optimize the selection of flows transmitted to the gateway, D-UFP takes into account possible dependencies between flows. We show that D-UFP is more difficult than NP-hard problems for which no good approximation is known. Then, we address two special cases of this problem: the case where all the sensors have a shared channel and the case where the sensors form a mesh and route to the gateway over a spanning tree.
Keywords: Approximation algorithms; Approximation methods; Bandwidth; Logic gates; Radar; Vectors; Wireless sensor networks; Dependent flow scheduling; sensor networks

Dynamic reliability management: Reconfiguring reliability-levels of hardware designs at runtime - Anwer, Jahanzeb; Meisner, Sebastian; Platzner, Marco (Reconfigurable Computing and FPGAs (ReConFig), 2013 International Conference on)
Keywords: fault tolerant computing; field programmable gate arrays; logic design; reliability; BYU-LANL tool; DRM tool flow; FPGA based hardware designs; avionic application; device technologies; dynamic reliability management; fault-tolerant operation; hardware designs; reconfiguring reliability levels; space applications; Field programmable gate arrays; Hardware; Redundancy; Reliability engineering; Runtime; Tunneling magnetoresistance